2020
DOI: 10.5530/pj.2020.12.91
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Stability Indicating HPLC Method for Determination of Caffeic Acid, Vitexin and Rosmarinic Acid in Thunbergia laurifolia Leaf Extract

Abstract: Thunbergia laurifolia has been a popular herb used in Thai traditional medicine for detoxification and as antipyretic. It contains rosmarinic acid (RA), caffeic acid (CA) and vitexin as major compounds. In order to control the herbal quality, the stability indicating high-performance liquid chromatography (HPLC) was developed and validated. The stability study of compounds in T. laurifolia leaf extract was investigated. The chromatographic separation was performed using a reversed-phase C18 column and mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…No significant changes were observed in the antioxidant activity of nanoemulsions loaded with vitexin during storage for 45 days at all temperatures. This result corresponded to a report that vitexin was stable at room temperature for up to 3 months, with slight decomposition observed at 40 °C 58 . It can be suggested that the formulated nanoemulsion maintained the antioxidant property of vitexin during storage.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…No significant changes were observed in the antioxidant activity of nanoemulsions loaded with vitexin during storage for 45 days at all temperatures. This result corresponded to a report that vitexin was stable at room temperature for up to 3 months, with slight decomposition observed at 40 °C 58 . It can be suggested that the formulated nanoemulsion maintained the antioxidant property of vitexin during storage.…”
Section: Resultssupporting
confidence: 90%
“…This result corresponded to a report that vitexin was stable at room temperature for up to 3 months, with slight decomposition observed at 40 °C. 58 It can be suggested that the formulated nanoemulsion maintained the antioxidant property of vitexin during storage. The emulsifiers used to fabricate these nanoemulsion systems, Tween 80 and lecithin, also contributed to the antioxidant properties and provided synergistic scavenging of the encapsulated vitexin.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Chromatography was achieved using Purospher ® RP-18 end-capped HPLC column (250 cm×4.6 mm, 5 μm) from Merck KGaA (Darmstadt, Germany). The mobile phases consisted of 0.5% acetic acid in deionized water and methanol with a gradient elution according to Woottisin et al (16). A constant flow rate of 1.0 ml/min was conducted throughout the analysis with temperature control at 25˚C.…”
Section: High-performance Liquid Chromatography With Diode Array Dete...mentioning
confidence: 99%
“…Polyphenols are believed to possess the capacity to scavenge free radicals due to their reducing abilities, as they can serve as donors of hydrogen or electrons. As indicated by Woottisin et al (2020), these extracted phenolic compounds, which are secondary metabolites produced by plants, have various positive effects on human health and are directly associated with their antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%